Santau and Malay Society: An Analysis from the Perspective of Islamic Aqidah: (Santau dan Masyarakat Melayu: Analisis dari Perspektif Akidah Islam) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2013)
Santau has been a practice since long ago. Some of the practices derive from a kind of black magic that was learnt specifically for the benefit of the practitioner and his family. However, the function of santau has altered due to some changes in attitude and in ways of thinking. Nowadays, santau is usually used to destroy and harm other people. Although its application has declined due to increased religious consciousness, it still continues to exist in the Malay community. Therefore, this article tries to describe santau as practiced in Malay society. The area of Santan in the state of Perlis was selected as the location for this research because it has been known to be a focal point for santau and its practitioners. In addition, the purpose of this study is also to examine the religious discussions concerning this practice and aqidah from the perspective of the Qur'an and sunnah.Keywords: santau, black magic, aqidah, Perlis, Malay community